Informal and Formal Sector Participation and Earnings in a LDC: The Importance of Time and Migration - Peter Karpestam (Lund University, School of Economics and Management, Department of Economics, 2011)
Theoretical and empirical research points to potentially different patterns of labor recruitment and importance of social networks in the formal and informal sector. The paper touches upon this topic and investigates the conjecture that employment chances and expected earnings depend differently on individuals' allocation of time and mobility patterns in the informal and formal sector. This is investigated in a LDC context using a household survey from Guatemala (Encovi 2000). The results suggest that the probability to obtain employment in agriculture (informal sector) increases with the amount of time spent at the current residence. The results are reversed for (informal) uncovered wage workers. For the (informal) self-employed and the formal sector (covered wage workers) the results does not display any evident patterns. Merging all segments of the informal sector, the results show that expected earnings in the informal sector are slightly reduced by time not spent at the current residence.
Keywords: D13; J60; J70; O17; R23; 330; The Informal Sector; Labor; Migration; Time; Central America; Guatemala.